2020
DOI: 10.1101/2020.03.18.995316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cross-kingdom conserved ER-phagy receptor maintains endoplasmic reticulum homeostasis during stress

Abstract: 2Eukaryotes have evolved various quality control mechanisms to promote proteostasis in the ER.3 Selective removal of certain ER domains via autophagy (termed as ER-phagy) has emerged as a 4 major quality control mechanism. However, the degree to which ER-phagy is employed by other 5 branches of ER-quality control remains largely elusive. Here, we identify a cytosolic protein, C53, 6 that is specifically recruited to autophagosomes during ER-stress, in both plant and mammalian cells. 7C53 interacts with ATG8 vi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 64 publications
0
44
0
1
Order By: Relevance
“…Indeed, previous studies have observed an altered pattern of UFMylation in the absence of CDK5RAP3 leading to the suggestion that it may be a substrate adaptor 52 . Interestingly, CDK5RAP3 was suggested to function as a sensor for ER stress to induce autophagic degradation of aberrant proteins formed as a result of ribosomal stalling 67 . Several multidomain and multiprotein E3 ligases such as PARKIN and Cullin Ring Ligases (CRLs) are inhibited and their activation is a carefully orchestrated multistep process 35, 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have observed an altered pattern of UFMylation in the absence of CDK5RAP3 leading to the suggestion that it may be a substrate adaptor 52 . Interestingly, CDK5RAP3 was suggested to function as a sensor for ER stress to induce autophagic degradation of aberrant proteins formed as a result of ribosomal stalling 67 . Several multidomain and multiprotein E3 ligases such as PARKIN and Cullin Ring Ligases (CRLs) are inhibited and their activation is a carefully orchestrated multistep process 35, 68 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, ubiquitin-interacting motif (UIM) has been reported to mediate the binding between ubiquitin binding protein RPN10 and ATG8 for proteasome degradation [53]. Another study also demonstrated that a reticulophagy receptor c53 contains a shuffle AIM for ATG8 binding [61]. Of note, both UIM and shuffle AIM have also been identified in mammals.…”
Section: Decision Of Cargo Sequestration and Autophagosome Formation: A Competition Mode For Atg8 Binding Specificity And Plasticity Betwmentioning
confidence: 99%
“…库 [1] 。植物中存在多种形式的叶绿体自噬,主要取决于叶绿体的状态或植物所处 的状态。在光胁迫下,UVB(ultraviolet B)造成拟南芥叶绿体破坏,而损伤的 整个叶绿体可以通过依赖于 ATG8 脂化的途径被包裹到自噬泡中, 然后转运到液 泡中降解 [26] 。 碳 饥 饿 下 , 叶 绿 体 中 Rubisco ( Ribulose-1,5-bisphosphate carboxylase/oxygenase)蛋白也可直接被包裹(RCBs,Rubisco-containing bodies) 转移至液泡中,通过依赖于 ATG 基因的自噬途径降解 [27] ,如拟南芥 atg5 突变体 中,自噬的形成被抑制,同时也抑制了 RCBs 在液泡中的积累 [28] 。但 RCBs 的形 成及运输还有待进一步研究,一种推测是 RCBs 通过叶绿体基质间微管被切割再 经 ESCRT(Endosomal sorting complexes required for transport)途径运输,从质 体中凸起形成 [1] 。拟南芥 ESCRT-III 亚基 chmp1(Charged multi-vesicular body protein 1)突变体表现出质体微管结构异常,基质与质体包膜蛋白的降解减少, 吞噬泡闭合延迟、胞质 RCBs 积累,表明 CHMP1 可能通过促进吞噬泡的闭合、 传递 RCBs 进入液泡被降解 [29] 。叶绿体自噬还可以受植物特异性蛋白 ATI1/2 (ATG8 interacting protein 1/2)介导,它们定位于细胞质体和内质网,而在碳饥 饿或盐胁迫期间转移至细胞质中 [30,31] 。碳胁迫下,位于质体上的 ATI1 通过两个 AIM 结构与 ATG8f 互作, 可以靶向质体通过选择性自噬转移至液泡降解 [31] 。 RCBs 与 ATI1 介导的选择性自噬都作用于叶绿体蛋白,RCBs 主要作用于基质蛋白, ATI1 介导的质体选择性自噬主要作用于来自叶绿体外膜或类囊体膜的蛋白 [1] 。 此 外,受损的叶绿体外膜蛋白可被泛素化,再被未知的自噬受体识别通过选择性自 噬降解 [32] 。 有报道表明定位于细胞质的 E3 泛素连接酶 PUB4 (Plant U-Box protein 4)参与叶绿体膜蛋白的泛素化,但尚未明确 PUB4 的具体靶点 [33] ;且 PUB4 不 是诱导叶绿体自噬的必要条件,在拟南芥 pub4 突变体中,强光和低温处理可以 诱导叶绿体自噬 [34] 物酶体, 且与 ATG8 共定位, 说明损伤的过氧化物酶体可能被自噬选择性降解 [35] ; 此外,在非胁迫条件下,拟南芥 atg 突变体与野生型相比积累更多的过氧化物酶 体,说明植株正常生长中过氧化物酶体的丰度也受选择性自噬调控 [35] 。哺乳动 物中过氧化物酶体自噬需要选择性自噬受体 p62/SQSTM1 (p62/Sequestosome-1) 、 NBR1(Next to brca1 gene 1 protein)结合泛素化的过氧物酶体表面蛋白 PEX5 (Peroxin-5-related protein)或 PMP70(Peroxisomal membrane protein 70)参与, 但植物中 NBR1 暂未报导参与过氧化物酶体自噬过程 [36,37] 。此外,拟南芥中发 现 PEX6 与 PEX10 蛋白通过 AIM 结构可直接与 ATG8 互作,说明这二者可能参 与介导过氧化物酶体自噬 [38] 。细胞内自然降解的蛋白或者非生物胁迫下受损的 错误折叠蛋白聚集后会导致聚集体自噬, 聚集的蛋白被泛素化后可以通过选择性 自噬受体 NBR1(烟草中为 Joka2)被自噬降解 [39,40] 。拟南芥和番茄 NBR1 缺失 植株表现出热胁迫和氧化胁迫敏感, 这可能与错误折叠的泛素化蛋白过多积累而 不能通过选择性自噬降解有关 [41,42] 。营养缺乏等胁迫条件下,失活以及错误折 叠的蛋白质过量积累往往导致内质网应激,诱发内质网自噬 [43] 。拟南芥 ATI1/2 是植物中最早报导介导内质网自噬的选择性受体 [30] ,近来更多的内质网自噬选 择性受体被鉴定,包括拟南芥 Sec62(Translocation protein SEC62) 、玉米 Rtn1/2 (Reticulon homology domain (RHD)-containing protein 1/2) 、 拟南芥 C53 等 [44][45][46] 。 线粒体作为有氧呼吸的主要场所, 在植物面对胁迫时会产生大量的活性氧 (ROS, Reactive oxygen species) ,因此线粒体自噬对于在胁迫下维持线粒体稳态至关重 要 [47] 。UVB 造成叶绿体破坏的同时也会导致线粒体紊乱,拟南芥 atg5、atg7 突 变体叶片中由 UV...…”
Section: 叶绿体, 而且还为植物提供了一个在衰老和饥饿期间可以重新调动氮和碳的储存unclassified